Survey on Cognitive Radio Green Network with Cross-Layer Technology - Jiao Wang; Junhui Zhao; Jiajiao Du (Dianxin kexue)
Applications of the cognitive radio technology based on cross-layer in green networks with the aim of saving energy were explored. A variety of key technologies on cognitive radio based on cross-layer protocol in green network were collected and discussed. First, the spectrum of architecture and cross-layer structure on cognitive radio network were discussed; second, a large number of cognitive radio cross-layer solutions were discussed to make energy-saving target contrast; third, the key challenges were pointed out and possible solutions for cross-layer cognitive radio technology in green network were provided.